The Impact of corporate Hedging Strategy on Stock Return Volatility - Zahid, Putra Faizurrahman; Baharuddin, Mohamad Hanif; Ramzi, Mohammad Ikram (International Journal of Accounting, Finance and Business, 2025)
This study examines the relationship between stock return volatility and corporate hedging strategies in the context of Malaysia's plantation industry. This study intends to identify the causal relationships between hedging and stock return volatility by using the plantation industry companies in Malaysia become the subject of analysis with two developments of subsamples, hedgers and non-hedgers from 2011 till 2023. The methodology measures the effect of hedging actions on stock return volatility by using panel data and Heckman estimation models. Application of hedging by using derivative such as futures, options, swaps and forwards are expected to reduce stock return volatility. Furthermore, the research aims to pinpoint the event effect in which being segregated by pre- and post-strike event of COVID-19 pandemic. The analysis result showing corporate hedging has significant effect on stock return volatility. The robustness of the control variables; firm size, leverage, growth, foreign exposure are found significant, while liquidity and financial performance effects are non-significant. The study also shows the additional reduction evidence of stock return volatility on the COVID- 19 outbreak crisis, but the result is non-significant